Proposta de método para mensuração e avaliação dos custos de transação sobre compras públicas - Fim, Cristiano (2015)
This study focuses its aim in proposing a method for measurement and analysis of transaction costs incurred when executing public procurement processes. Theories of Economics of Transaction Costs, Business Process Management and Activity Based Costing were used. The results provide a monetary and situational diagnosis in light of the Transaction Costs Theory, as well as demonstrating the existence of asymmetry among values measured of transaction costs and motivating factors of costs and the volumes of operational activities of procurement departments studied